2013
DOI: 10.3892/mmr.2013.1821
|View full text |Cite
|
Sign up to set email alerts
|

Co-culture of human nucleus pulposus cells with multipotent mesenchymal stromal cells from human bone marrow reveals formation of tunnelling nanotubes

Abstract: Abstract. Degeneration of the intervertebral disc (IVD) is the main cause of age-related damage of spinal tissues. Using multipotent mesenchymal stromal cells (MSCs) regenerative medicine intends to restore the IVD components of annulus fibrosus (AF) and nucleus pulposus (NP). In the present study NP cells (NPCs) and MSCs obtained from adolescent patients suffering from scoliosis were used. IVDs and vertebrae were obtained during surgery and subsequently processed in order to establish cultures of NPCs and MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Therefore, DiO-type lipophilic dyes may be transferred and incorporated by unlabelled cells. Our previous studies revealed a similar phenomenon of DiO and DiD transfer between MSCs and NPCs in heterotypic co-culture (13). Using a fluorescent microscope, rapid movements of DiO and DiD particles in SW-1353 cells were detected (data not shown; video recording available on request from the corresponding author).…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…Therefore, DiO-type lipophilic dyes may be transferred and incorporated by unlabelled cells. Our previous studies revealed a similar phenomenon of DiO and DiD transfer between MSCs and NPCs in heterotypic co-culture (13). Using a fluorescent microscope, rapid movements of DiO and DiD particles in SW-1353 cells were detected (data not shown; video recording available on request from the corresponding author).…”
Section: Resultssupporting
confidence: 54%
“…In our previous study, a predominance of DiD-stained cells over DiO-stained cells was observed by flow cytometry, which we termed ‘Q1-Q4 asymmetry’ (13). In the present study, homotypic co-cultures of SW-1353 cells were performed to precisely quantify the Q1-Q4 asymmetry.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations